The clearing - West, Palmer; Smith, Jonah; Brugge, Pieter Jan; Haythe, Justin, 1973-; Redford, Robert; Mirren, Helen; Dafoe, Willem; Nivola, Alessandro; Craven, Matt; Sagemiller, Melissa, 1974-; Crewson, Wendy; Lenoir, Denis, 1949-; et al. ([United States] : 20th Century Fox Home Entertainment, 2004)
A successful businessman is kidnapped by a mysterious man, who is disturbingly familiar with the intimate details of his prisoner's personal life.
Originally produced as a motion picture in 2004.
Special features: optional audio commentary by Brugge, Haythe & Tent; 8 deleted scenes, with optional audio commentary by Brugge, Haythe & Tent (16 min. total); full length screenplay with 300 stills; theatrical trailer (2 min.).
Title from container.
Not viewed.
Sources used: Copyright catalog online; Internet movie database WWW site, viewed 2010-08-19.
Director of photography, Denis Lenoir ; film editor, Kevin Tent ; music composed by Craig Armstrong.
Keywords: Kidnapping -- Drama; Thrillers (Motion pictures); Feature films; Fiction films